Effect of novel alkaline copper slurry on 300 mm copper global planarization - 刘伟娟 刘玉岭 王辰伟 陈国栋 蒋勐婷 袁浩博 程鹏飞 (Journal of semiconductors, 2014)
The copper removal rate and uniformity of two types copper slurries were investigated, which was performed on the 300 mm chemical mechanical planarization （CMP） platform. The experiment results illustrate that the removal rate of the two slurries is nearly the same. Slurry A is mainly composed ofa FA/OI1 type chelating agent and the uniformity reaches to 88.32%. While the uniformity of slurry B is 96.68%, which is mainly composed of a FA/OV type chelating agent. This phenomenon demonstrates that under the same process conditions, the uniformity of different slurries is vastly different. The CMP performance was evaluated in terms of the dishing and erosion values. In this paper, the relationship between the uniformity and the planarization was deeply analyzed, which is mainly based on the endpoint detection mechanism. The experiment results reveal that the slurry with good uniformity has low dishing and erosion. The slurry with bad uniformity, by contract, increases Cu dishing significantly and causes copper loss in the recessed region. Therefore, the following conclusions are drawn： slurry B can improve the wafer leveling efficiently and minimize the resistance and current density along the line, which is helpful to improve the device yield and product reliability. This investigation provides a guide to improve the uniformity and achieve the global and local planarization. It is very significant to meet the requirements for 22 nm technology nodes and control the dishing and erosion efficiently.